INSTRUCTIONAL DESIGN OF DESCRIPTIVE TEXT MATERIALS BASED ON PALEMBANG LOCAL CULTURE BY IMPLEMENTING LSLC FOR STUDENTS TO UNDERSTAND LEARNING - Nurlista Iryanti; Rita Inderawati; Soni Mirizon (University of Kuningan, 2021)
Lesson study learning community (LSLC) is one of the various innovations to make students have a good quality in learning in this 21st-century era. The objective of the study was to produce a learning trajectory in English which can help students in learning descriptive text material through LSLC in the classroom. This study used design research method type validation study. The participants were 32 seventh-grade students and English teachers of SMP Negeri 18 Palembang. The data were collected through interview, observation, documentation, and field notes. The results of the study revealed the teachers did not implement the application of lesson study learning community based on the appropriate stages. Somehow, in the process of lesson study, some difficulties were discovered. From the result of interview and observation, some problems in implementing were still found due to the limitation of the time, and the teacher’s commitment during the implementation. However, the lesson study helps students to understand learning through collaboration.